Methodology of the Multi-Disciplinary Problem: The Border and Socio-Cultural Interaction Approach - Osmond Agbor, Otora (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
The paper examines borders as regions lying along and astride the international frontiers separating one nation-state from another and sub-national areas whose economic and social life are directly and significantly impacted by proximity to an international boundary. It argues that beyond the town or district, there is a wider territory (of borderlands) usually described as a region, where regional consciousness is a reality. The study adopts the social studies approach which cuts across demarcation between disciplines and suggests a holistic approach using the participatory integrative methodology to the investigation of human problems. Findings did not only indicate the porous and artificial nature of the borderlands but also adds the psychological angle which reflects the mental predisposition of the border inhabitants towards a situation where man attempts to divide a culturally homogenous group of people into separate entities. The reasons are not only political and economic impositions by the main culture over the subculture but also a reflection of the supremacy of the imperialistic bureaucratic majority over the colonized underprivileged minority. The conclusion reflects the need for schools, colleges and universities to protect data to enhance border and social research.